Impaired emotion processing and a reduction in trust in patients with somatic symptom disorder - Erkic, Maja; Bailer, Josef; Fenske, Sabrina C.; Schmidt, Stephanie N. L.; Trojan, Jörg; Schröder, Annette; Kirsch, Peter; Mier, Daniela (Clinical psychology & psychotherapy, 2018)
There is accumulating evidence for deficits in the perception and regulation of one's own emotions, as well as the recognition of others' emotions in somatic symptom disorder (SSD). However, investigations of SSD focusing on specific aspects of emotion processing and how these might interact are missing. We included 35 patients with SSD and 35 healthy controls who completed questionnaires on the perception and regulation of their own emotions, as well as experimental investigations of emotion recognition and trust. In line with previous studies, our results show that SSD patients in comparison to healthy controls have difficulties in the identification and description of own feelings (ηp2 = .381 and ηp2 = .315). Furthermore, we found that patients apply less cognitive reappraisal (ηp2 = .185) but tend to use more expressive suppression (ηp2 = .047). In contrast to previous studies, we found SSD patients to perform superior in emotion recognition, in particular for anger (d = 0.40). In addition, patients with SSD invested less in a trust game (d = 0.73). These results point to a higher sensitivity for negative emotions and less trust in others. Further, these findings suggest a dissociation between the ability to recognize one's own emotions versus others' emotions in SSD. Future interventions targeting emotion processing in SSD might focus on the identification of one's own emotions, prior to the training of emotion regulation.
Gesehen am 29.11.2018
First published: 18 October 2017